Metacognition and critical thinking - Rupnik Vec, Tanja (Šolsko polje, 2007)
The purpose of this article is to answer the following questions: (a) What is metacognition?, (b) How are metacognition and critical thinking related?, (c) How can teachers stimulate, direct and support the development of metacognitive and - indirectly - critical thinking in their students? The first question is in the heart of many contemporary studies of cognitive and developmental psychology. In the search for an answer to this question we are not satisfied with the general definition of the concept, such as 'metacognition is the thinking about thinking'; rather we investigate in detail how some authors conceptualize it. In the second part of the article weinvestigate the relationship between metacognition and critical thinking, as conceptualized from the perspective of some authors from the field of education. On this basis, we make the conclusion about metacognition as an important element of critical thought. In the third section we are pragmatic and suggest concrete strategies for enhancing metacognition that teachers could use as they teach various contents and apply different methods (debate, role play, problem solving, case studies etc.).
Keywords: kritično mišljenje; metakognicija; metodika; pouk; učenje